A critical appraisal of mucormycosis in COVID- 19 patients in a tertiary care centre in India - Sujata Raychaudhuri; Juhi Taneja; Jaseetha Sasidharan; Mukta Pujani; Kanika Singh; Tathagata Chatterjee; Manjula Jain; Rajkumar Chandoke; Anil Rai; Zafar Abbas; Asim Das (Current Medical Mycology, 2023)
Background and Purpose: Morbidity and mortality of opportunistic fungal infections in COVID-19 patients are less studied and defined. The patients receiving immunosuppressive therapy, broad-spectrum antibiotics, corticosteroids, and invasive and non-invasive ventilation are the high-risk groups.Materials and Methods: The demographic profile as well as clinical and radiological findings of all the patients with COVID-19 suspected of Mucormycosis (MM) were recorded. The tissue samples from all the patients were sent for microbiological (KOH mount and culture) and histopathological analysis for confirmation of MM.Results: In total, 45 COVID-19 patients suspected of MM were included in the study an MM was confirmed in 42 patients. The mean age of the patients was 50.30±14.17 years with a female: male ratio of 1.1:1. The most common symptom was headache (52.38%) followed by purulent nasal discharge (38.09%) and facial pain in 33.33% of the cases. The ocular symptoms included a diminution of vision (33.33%) and redness of the eye (2.38%).The most common site of involvement was rhino-orbital (42.85%) followed by sinonasal (23.80%) and rhino cerebral (19.04%). Majority (38.09%) of the patients were diagnosed with stage II of Rhino-orbital-cerebral Mucormycosis (ROCM) based on radiology. A history of diabetes mellitus and steroids was present in 97.61% and 85.71% of the cases, respectively. Moreover, KOH was positive for MM in 97.61% of the cases while the culture was positive in only 35.71% of the cases. In addition, on histopathology, MM was confirmed in 64.28 % of the cases. Mixed growth with Aspergillus species and Rhizopus species was observed in 14.28% of the cases in culture and 11.90% of the cases in histopathology test. Furthermore, angioinvasion was found in 23.80% of the cases according to the histopathology test.Conclusion: Based on the results, the most common conditions associated with MM in COVID-19 patients were diabetes mellitus and steroid therapy. A high level of clinical suspicion aided with diagnostic tests, including KOH mount, culture, histopathology, and radiology which helped the early detection of opportunistic fungal infection in COVID-19 patients to ensure timely treatment.